Cytokine Storm in COVID-19: “When You Come Out of the Storm, You Won’t Be the Same Person Who Walked in” - Castelli, Vanessa; Cimini, Annamaria; Ferri, Claudio (Frontiers in Immunology, 2020)
In December 2019 a novel coronavirus, indicated as COVID-2019, was discovered as the causal agent of a severe respiratory infection named SARS-CoV-2, which was recognized as worldwide pandemic. There are still numerous doubts concerning its pathogenesis and particularly the underlying causes of the various clinical courses, ranging from severe manifestations to asymptomatic forms, including the acute respiratory distress syndrome. The major responsible of acute respiratory distress syndrome is the so called “cytokine storm”, an aberrant response from the host immune system, that induce an exaggerated release of proinflammatory cytokines/chemokines. In this review, we will discuss the role of cytokine storm in COVID-2019 and the potential treatments to counteract this aberrant response, which may be valuable in the clinical translation.